A new genus of the tribe Aemodogryllini (Orthoptera, Rhaphidophoridae, Aemodogryllinae) from China - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2017)
In this paper, a new genus Gymnaetoides gen. nov. is described for the new species Gymnaetoides testaceus sp. nov. from Zhejiang. Therefore, two new combinations of this genus result, including Gymnaetoides indivisus (Zhang & Liu, 2009) comb. nov. and Gymnaetoides acutilobatus (Gorochov, 2010) comb. nov.. A key to the species of Gymnaetoides gen. nov. is provided.